Estimated Cost to a Commercial Feedlot of a Quarantine - Stroade, Jeri; Schroeder, Ted C. (Kansas State University. North American Institute for Beef Economic Research, 2010)
Potential introduction of contagious foreign animal diseases in the US has escalated in recent years with increased global commerce and travel and concerns about bioterrorism. In the event of a contagious animal disease outbreak, animal health department emergency management plans generally include animal movement restrictions and livestock operation quarantines. As emergency management plans are designed, understanding probable costs to industry participants of various disease management schemes is critical to developing economically efficient crisis management strategies. The purpose of this report is to demonstrate, with an example, probable costs associated with cattle quarantined in a commercial cattle feedlot in Southwestern Kansas.
Keywords: Cattle; Disease; Feedlot; Costs; Kansas; Emergency management